Scheduling Optimization For Extract, Transform, Load (ETL) Process On Data Warehouse Using Round Robin Method (Case Study: University Of XYZ) - Berliantara, Agung Yudha; Wicaksono, Satrio Agung; Pinandito, Aryo (Faculty of Computer Science (FILKOM) Brawijaya University, 2017)
ETL scheduling is a challenging and exciting issue to solve. The ETL scheduling problem has many facets, one of which is the cost of time. If it is not handled correctly, it may take a very long time to execute and inconsistent data in very large data. In this study using Round-robin algorithm method that proved able to produce efficient results and in accordance with conventional methods. After doing the research, the difference between these two methods is about execution time. Through this experiment, the Round-robin scheduling method gives a more efficient execution time of up to 61% depending on the amount of data and the number of partitions used.